Sleep hygiene efficacy on quality of sleep and mental ability among insomniac patients - Sivasankari Varadharasu; Niyati Das (Journal of Family Medicine and Primary Care)
Background Insomnia affects both quality of life and productivity at work, and it raises the risk of other diseases, such as depression, that coexist with insomnia. Nowadays, it is highly advised to treat insomnia with behavioral and psychological therapeutic methods to ensure the quality of your sleep. Aim This study aimed to find the efficacy of sleep hygiene techniques in improving sleep quality and mental ability among insomnia clients. Methods Self-structured questionnaires used to evaluate sleep quality and the McQuaig Mental Ability Test to test mental ability were used to collect data during the study’s six-week duration, which involved the recruitment of 50 participants using a purposive sample technique. A paired sample t-test and Pearson correlation were used for the statistical analysis. Results Data analysis shows that sleep quality (t = 33.35) (P = 0.0000) and mental ability (t = 35.33) (P = 0.0001) are both highly significant at P =0.0001. Correlation regression data of sleep hygiene elements such as schedule, avoiding caffeine and beverages, relaxation routine, and sleep-stimulating environment shows that there is a positive correlation with the quality of sleep at r = 0.9, 0.89, 0.75, and 0.68, whereas P = 0.000, 0.01, and 0.023, respectively. Similar to this, there is a positive association between mental ability and good sleep habits such as a relaxing routine, a sleep-promoting environment, and a schedule with r = 0.91, 0.88, and 0.92, respectively, with P values of 0.0001, 0.001, and 0.001. Conclusion The results of the study provide compelling evidence that good sleep hygiene can help enhance insomniacs’ mental ability and sleep quality. Furthermore, those with moderate levels of sleep quality, those between the ages of 18 and 38, and those with higher education benefited more than others.